Alcohol-attributable deaths among indigenous and non-indigenous Australians - Zhao, Yuejen; Li, S.; Chikritzhs, Tanya (Open Access Publishing London (OAPL), 2013)
Introduction: Alcohol abuse in Indigenous communities in Australia has been a devastating problem. The association between alcohol use and ill-health is well established but complex. The aim of this review was to assess and compare alcohol-attributable deaths and years of life lost among Indigenous Australians to the Australian population as a whole. Methods and materials: Standard burden of disease and injury methodology and population attributable fractions were applied to analyse death registration data from 2003 to 2006. Alcohol use prevalence was retrieved from the 2004/5 Australian National Health Surveys and the National Aboriginal and Torres Strait Islander Health Survey. The relative risk estimates were compiled from epidemiological reviews. Results: The results found that Indigenous Australians experienced 7% to 7.5% mortality burden resulting from alcohol use, and were over-represented in comparison with their population share (2.5%). At ages 15 to 74 years, the alcohol-attributable deaths and years of life lost rates among Indigenous Australians were over 2–3 times higher than in the average across all Australians. At ages 25 to 54, the alcohol-attributable mortality rates among Indigenous Australians were 4–6 times higher than the national average. Alcohol-attributable mortality risk was substantially (2–3 times) higher among males than females, regardless of ethnicity and age group.Discussion: This review provides new and more reliable national data on alcohol-attributable deaths and alcohol-attributable years of life lost, comparing Indigenous Australians with the general population. Significant mortality and morbidity among Indigenous Australians is associated with excess alcohol use, which generally occurs within a historical context and socioeconomic disadvantage. The failure to address poverty in Indigenous communities is likely to undermine gains that might otherwise occur through traditional prevention activities, such as alcohol restrictions. Conclusion: It was evident that the harmful use of alcohol contributed to the disproportionate mortality burden experienced by Indigenous Australians.